2018
DOI: 10.1177/0269881118780011
|View full text |Cite
|
Sign up to set email alerts
|

Weight change over two years in people prescribed olanzapine, quetiapine and risperidone in UK primary care: Cohort study in THIN, a UK primary care database

Abstract: Olanzapine is more commonly prescribed to people with lower weight. However, after accounting for baseline weight, age, sex and diagnosis, olanzapine is still associated with greater weight gain over two years than risperidone or quetiapine. Baseline weight does not ameliorate the risks of weight gain associated with antipsychotic medication. Weight gain should be assertively discussed and managed for people prescribed antipsychotics, especially olanzapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…In the long-term, contrary to one previous finding (Haddad, 2005), we found that weight gain did not stabilize during four years of follow up. However, our finding of long-term effect of weight gain is consistent with previous studies by Bushe et al (2012) and Osborn et al (2018), but we are able to quantify the effect more accurately. Previous research has suggested women’s weight is more affected by AP exposure (Seeman, 2008); however, we found that only olanzapine (in the long-term) and quetiapine (in the long and short-term) induced more weight gain in women.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the long-term, contrary to one previous finding (Haddad, 2005), we found that weight gain did not stabilize during four years of follow up. However, our finding of long-term effect of weight gain is consistent with previous studies by Bushe et al (2012) and Osborn et al (2018), but we are able to quantify the effect more accurately. Previous research has suggested women’s weight is more affected by AP exposure (Seeman, 2008); however, we found that only olanzapine (in the long-term) and quetiapine (in the long and short-term) induced more weight gain in women.…”
Section: Discussionsupporting
confidence: 91%
“…A major advantage of our approach is that it includes pre-treatment weight change information, so patients act as their own controls in the analysis and any additional weight change after baseline is attributable to the AP treatment. The approach utilizes all individual weight records at their time of measurement, therefore avoiding the loss of information seen in previous studies which categorize outcomes or use period means or incidence rates as summary measures (Bak et al, 2014; Osborn et al, 2018). Our longitudinal model-based approach also accounts for missing weight records – assuming weight recording is missing at random within strata, conditional on observed weight measurements (Haneuse et al, 2016) – while incorporating informative pre-baseline weight data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations